Analisis Pemberian Upah Buruh Tani terhadap Pemenuhan Kebutuhan Hidup di Kecamatan Konang, Pamekasan - Jalal, Moh; Koemarullah, Agoes (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2025)
This study investigates the challenges faced by farm laborers in Konang, Pamekasan, regarding their wages and its impact on their livelihood, particularly from an Islamic economic perspective. Agriculture is a vital sector in many countries, and farm laborers play a crucial role, yet they often encounter significant issues with their remuneration. In Konang, a region where approximately 85% of the population works as rice farmers, wage systems vary, leading to disparities and low pay. The research highlights issues such as delayed wage payments (3-7 days after work completion), which cause financial instability and force laborers to seek additional work, affecting their health and children's education. Furthermore, the study reveals gender-based wage disparities, with female farm laborers often receiving lower pay for the same work as their male counterparts, reflecting gender inequality in the wage system. These issues are exacerbated by a lack of legal protection and awareness of labor rights, leading to the acceptance of unfair practices as tradition. The findings suggest that the current wage practices do not align with Islamic economic principles of justice, transparency, and welfare. This research employs a qualitative descriptive approach, utilizing library and field research, including in-depth interviews with five farm laborers in Konang. The study aims to understand the wage practices, evaluate them against Islamic economic principles, and analyze gender-based wage differences in Konang. The implications of this study point to the urgent need for policy interventions to ensure fair and timely wage payments, promote gender equality in remuneration, and enhance legal literacy among farm laborers. This research contributes to the understanding of labor issues in the agricultural sector within an Islamic economic framework, offering insights for improving the welfare of vulnerable communities.